Improvement of Convective Heat Transfer through Ultrasound Application: A Review - Flaih, Ayam; Abdali, Hussein; Hussein, Emad; Santos, Thiago (Anbar Journal of Engineering Science, 2025)
Enhancing heat transfer, particularly through convection, is crucial in various industrial applications, driving ongoing interest in methods to improve heat transfer rates and the efficiency of heat transfer equipment. Ultrasound has emerged as an effective and reliable method for boosting convective heat transfer, primarily due to the unique phenomena it creates within irradiated fluids, such as sound cavitation and streaming. In heat exchanges, where forced heat convection is typically the primary technique, ultrasound has shown notable effectiveness by improving convective heat transfer and reducing fouling. This paper summarizes recent research on the application of ultrasound in both forced and free convection heat transfer systems, emphasizing studies published in the past decade. Previous research has demonstrated that the influence of ultrasound on heat transfer varies significantly between laminar and turbulent flows, necessitating thoughtful consideration in system design. While progress has been made, gaps remain in understanding the influence of flow rates across systems and the thermal enhancement provided by ultrasound in gaseous systems. Furthermore, most research is conducted in experimental settings, highlighting the need for increased studies to support industrial applications.